Existential themes in the treatment of people at suicide risk. Understandings and practices of specialist healthcare professionals - Søberg, Ane Inger Bondahl (Mental health, religion & culture, 2018)
This qualitative study focuses on the ways in which existential themes were understood and addressed in therapeutic relationships with patients who had attempted suicide. Health care professionals (HCP) from Norway specialist healthcare participated in focus groups. The interviews were transcribed and analysed by systematic text-condensation through a four-step procedure. We found that the HCPs emphasised the context-specific functions of their departments. They considered these conversations essential but demanding. They indicated existential themes of hope/hopelessness, loneliness, meaning, life/death, shame, religion and suicide. The HCPs’ understandings of themes deemed to be existential and how they should be addressed were primarily based on clinical experience. This appeared to exacerbate the pressure on their personal involvement, leading to the question of whether patients’ existential needs are tackled or instead disappear into a conversational vacuum. The study suggests that HCPs' professional competence of existential themes pertaining to patients at suicide risk needs to be strengthened.